PARTISIPATIF DESAIN KAWASAN PERMUKIMAN PESISIR MASYARAKAT NELAYAN KELURAHAN LEATO SELATAN - Imran, Mohammad; Moha, Devie Indriyani; Tiagas, Doly Herling (Universitas Bina Taruna Gorontalo, 2023)
This research purpose are: (1) to identify the potential of the community in the participation or involvement in the design of fishing settlements on the coast; (2) exploring the potential of sustainable natural resources in existing settlements to apply the concept of a sustainable environment and a healthy environment. This research used a descriptive qualitative methods with the collaborative rationalistic community approach’s, with the location of a fishing settlement in RW 3, Leato Selatan Village. Field surveys were conducted in June – August 2022, starting with initial data collection followed by collaborative participatory methods with the community in the form of socialization, observation and design concepts from existing data. The results of this study show that the participation of the community along the coast of South Leato Sub-District is very large in involvement in data collection and design for their settlement area, their response is the potential possessed by the community, in addition to the potential of natural resources owned by the coast of South Leato which is in RW 3 also supports the implementation of design exploration with the concept of a healthy environment (sustainable environment). The conclusions of the research is that design participation in creating a sustainable environment and health environment requires cross-sectoral collaboration consisting of the community and academics (in this case researchers from Bina Taruna University, Gorontalo).